2016
DOI: 10.5194/se-7-469-2016
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of jute and coir blankets for erosion control in different field and laboratory conditions

Abstract: Abstract. Vegetation cover is found to be an ideal solution to most problems of erosion on steep slopes. Biodegradable geotextiles (GTXs) have been proved to provide sufficient protection against soil loss in the period before vegetation reaches maturity, so favouring soil formation processes. In this study, 500 g m −2 jute (J500), 400 g m −2 (C400), and 700 g m −2 coir (C700) GTXs were first installed on a 9 • slope under "no-infiltration" laboratory conditions, then on a 27 • slope under natural field condit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Smets et al [45] performed a review on the ability of geotextiles in reducing runoff and soil erosion, based on laboratory studies, analyzing several factors, as plot length, cover percentage, slope gradient, rainfall duration and intensity, and geotextile type. Similar field and laboratory tests have been carried out by Kalibová et al [46,47]. Field studies on jute and jute mats have been performed by Mitchel et al [48] to demonstrate their effectiveness for controlling erosion and runoff.…”
Section: Introductionmentioning
confidence: 81%
“…Smets et al [45] performed a review on the ability of geotextiles in reducing runoff and soil erosion, based on laboratory studies, analyzing several factors, as plot length, cover percentage, slope gradient, rainfall duration and intensity, and geotextile type. Similar field and laboratory tests have been carried out by Kalibová et al [46,47]. Field studies on jute and jute mats have been performed by Mitchel et al [48] to demonstrate their effectiveness for controlling erosion and runoff.…”
Section: Introductionmentioning
confidence: 81%
“…Given the rather steep plot slopes (more than 60%) and the moderately high Imax values, this result is remarkable. In similar studies, the erosion rate from jute net was found to be highly controlled by the plot slope, with high effectiveness values (99%) in case of slopes less than 30° (Kalibová et al, 2016), and with extremely low efficiency in case of steep slope (60°) (Álvarez Mozos et al, 2014). However, numerous studies have confirmed that jute net typically results in positive soil loss reduction compared to the control in both field and laboratory conditions (Mitchell et al, 2003;Álvarez Mozos et al, 2014).…”
Section: Discussionmentioning
confidence: 88%
“…Jute is a natural organic fiber that is also ecofriendly. It was widely used in combination with vegetation to control erosion of exposed soil (Kalibová et al 2016). Jute fiber was available in two different varieties woven and nonwoven and possessed a high degree of flexibility with a small percentage of elongation at break.…”
Section: Introductionmentioning
confidence: 99%